Quantitying snow conditions of World Cup alpine ski racing tracks - Wolfsperger, F.; Hinterberger, B.; Christian, J.; Matzl, M.; Jahnel, R.; Spörri, J.; Kröll, J.; Gilgien, M.; Rhyner, H.; Schneebeli, M.; Müller, E. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Changing snow conditions are considered a potential key injury risk factor among World Cup (WC) alpine ski racing stakeholders (Spörri et al., 2012). The purpose of this study was to quantify spatial and temporal variations in snow conditions within each monitored racing track as well as to detect differences between the six analyzed WC races. The quantified snow conditions were compared with the quality of the racing tracks as perceived by the athletes.